Clinical Evaluation of 6-Month Efficacy of 40% in-Office Whitening Treatment - Amar Piknjač; Dubravka Knezović Zlatarić (Association of Support to Oral Health Research (APESB), 2021)
Objective: To assess the 6-month efficacy of natural tooth color change in in-office bleaching treatment in terms of time by using a spectrophotometer. Material and Methods: A total of 20 participants were chairside treated with 40% hydrogen peroxide (HP), three applications each 20 minutes, in one appointment. Instrumental color measurement was performed on six anterior maxillary teeth before bleaching (baseline-t0), immediately after in-office bleaching and rehydration of the teeth (t1), 3 months (t2), and 6 months after bleaching treatment (t3). The spectrophotometer measured the tooth shades based on the CIE L*a*b* color notation system and Bleach index during the period of observation. CIE L*a*b* (ΔEab) color differences were calculated. Results: The color change at t1 was ΔEab = 3.2, at t2 was ΔEab = 1.8, at t3 was ΔEab = 1.2 and overall color change of in-office method was ΔEab = 3.6 (p<0.05). A significant effect for the mean CIEL*a*b* values was detected as within time b* values decreased significantly (p<0.05). Bleach index values significantly decreased during the time of observation, too (p<0.05). Conclusion: The in-office bleaching treatment using 40% hydrogen peroxide was effective, and the results showed a statistically significant decrease in color change during the period of 6-month observation.